2016
DOI: 10.1111/jfbc.12287
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Operational Stability of Acidic Proteases from Monterey Sardine (Sardinops sagax caerulea) Immobilized on a Partially Deacetylated Chitin Support

Abstract: Recovery of valuable compounds from by‐products generated from seafood processing represents an opportunity to produce value‐added products. Sardine acidic proteases were immobilized on partially deacetylated chitin through ionic linkages, using sodium tripolyphosphate as a support activating agent. Maximal enzyme activities of free and immobilized proteases were detected at pH 2, at which the immobilized form had higher stability than the free enzymes. Optimum temperatures for free and immobilized proteases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Also, the decrease in the specific activity may be due to the diffusional limitation of the substrate and product flow. Although GA creates very strong bonds between enzymes and carriers, it changes the structure of some enzymes during the binding process, causing loss of their activity (Salazar-Leyva et al, 2017).…”
Section: Characterization Of Free and Ch-mcementioning
confidence: 99%
See 3 more Smart Citations
“…Also, the decrease in the specific activity may be due to the diffusional limitation of the substrate and product flow. Although GA creates very strong bonds between enzymes and carriers, it changes the structure of some enzymes during the binding process, causing loss of their activity (Salazar-Leyva et al, 2017).…”
Section: Characterization Of Free and Ch-mcementioning
confidence: 99%
“…Pervez et al (2017) reported that immobilization decreases the inhibition of enzymes either by stabilizing the enzyme structure or by eliminating the inhibitor. Moreover, multipoint covalent attachment between the enzyme molecule and an activated carrier makes the structure of the enzyme more rigid, consequently decreasing conformational changes which can be induced by extreme pH (Salazar-Leyva et al, 2017). Narwal et al (2016) suggested that titratable acidity of milk should be between 0.19 to 0.25 % lactic acid equivalents (which correspond to pH from 5.0 to 6.5) at the time of adding an enzyme.…”
Section: Effect Of Ph and Ph Stability Of The Free And Ch-mcementioning
confidence: 99%
See 2 more Smart Citations
“…Chitosan is one of natural polymer (polysaccharides) derived from chitin by deacetylation process and has excellent biocompatibility, no toxicity, cheapness, high mechanical strength, and a susceptibility to chemical modi cations (Cahyaningrum and Sianita 2014;Salazar-Leyva et al 2017). One common approach for enzyme immobilization on chitosan is through multipoint covalent binding between the functional groups present on the surface of an activated chitosan by cross-linking agents such as glutaldehyde and the surface functional groups of the enzyme protein.…”
Section: Introductionmentioning
confidence: 99%